Optimizing MSE Partnerships: Assessing Partnership Intensity By Partnership Types - Amanda Anggi Purwanti; Feryanto; Nunung Kusnadi (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2025)
Partnership practices in Indonesia are highly diverse, encompassing various forms of support for Micro and Small Enterprises (MSEs), including capital, capital goods, marketing, and raw materials. This diversity reflects the Intensity of partnerships, a key determinant of collaboration effectiveness. High partnership intensity is expected to strengthen competitiveness, broaden market access, and accelerate business growth. Despite these potential benefits, participation of MSEs in partnerships remains relatively limited, highlighting the need for further investigation into their dynamics. This study aims to assess the Intensity of MSE partnerships in Indonesia by examining variations in both the number of partnership types adopted and their relevance to business needs. The analysis is based on secondary data from Statistics Indonesia's 2021 Micro and Small Industry Survey, covering 6,951 business units in the food and non-food sectors. Descriptive statistical methods were applied to map the distribution of partnership intensity across industries and business scales. The results show that small enterprises, particularly in the non-food sector, tend to have higher partnership intensity. In contrast, microenterprises in the food sector demonstrate limited involvement in multidimensional cooperation. These differences are influenced by managerial capacity, network access, and sector-specific needs. The findings underscore the importance of designing partnership strategies that are diversified and aligned with MSE needs to enhance effectiveness. This research contributes to understanding partnership intensity and provides policymakers with practical insights for supporting sustainable MSE development.